Uganda : Technical Assistance Report-Drafting the Public Finance Management Regulations. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report proposes draft regulations to address issues in the provisions of the Public Finance Management Bill 2012. The draft regulations propose a virement regime which serves to protect the composition of the budget, in particular prevention of virement between development and recurrent spending which will be particularly important in light of the new fiscal environment. It is also proposed to further strengthen the expenditure controls through a requirement to regularize excess expenditures through the contingencies fund and requiring reporting of outstanding payments.